(untitled) (Proceedings of the International Conference on Gender and Sexuality, 2023)
The present article addresses the exercise of sexual and reproductive rights by women incarcerated in the Americas. The State, through the use of police power, has the legitimacy to restrict the freedom of individuals who have violated laws. However, such restrictions on freedom not only serve the corrective function of penalties but also impact the reproductive and sexual rights of women prisoners. This is due to the construction of prisons, which disregards female bodies and their needs. The need for adequate apparatus and infrastructure to address women’s health demands, the exclusion of women’s sexual rights in many prisons, and the precarious nature of maternity in prison were studied. The article is based on a critical analysis of repressive criminal law, prioritizing imprisonment over alternative sentences, and disregarding the serious consequences of incarceration for women, especially considering the gender roles to which they are conditioned. The analysis focused on key situations, including intimate visits, breastfeeding, pregnancy, abortion, menstrual poverty, among other specific women’s health issues within the context of women’s prisons. The research employs an intersectional approach to study gender, race, social class, sexual orientation, religion, and other vulnerability factors. The main methodology adopted was qualitative bibliographical research, in order to build critical thinking through the analysis of the works of the main authors dealing with the subject.